2017
DOI: 10.1016/j.dadm.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of macrolinguistic aspects of narratives from individuals with Alzheimer's disease, mild cognitive impairment, and no cognitive impairment

Abstract: Introduction The depiction of features in discourse production promotes accurate diagnosis and helps to establish the therapeutic intervention in cognitive impairment and dementia. We aimed to identify alterations in the macrolinguistic aspects of discourse using a new computational tool. Methods Sixty individuals, aged 60 years and older, were distributed in three different groups: mild Alzheimer's disease (mAD), amnestic mild cognitive impairment, and healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
2
36
0
6
Order By: Relevance
“…In spite of the fact that the description of a complex picture is the most widely used task (Goodglass et al, 2000 ; Bschor et al, 2001 ; Cuetos et al, 2009 ; König et al, 2015 ), we observed that the description of a “working day” and “the last dream” seem to be more sensitive tasks, probably because require memory recall and a more structured narration. Some other researchers have investigated different aspects of language as communication abilities (Toledo et al, 2018 ), reading comprehension (Hudon et al, 2006 ; Schmitter-Edgecombe and Creamer, 2010 ), the repetition of complex sentences (König et al, 2015 ; Lust et al, 2015 ) or the ability to recognize the grammatical correctness (Taler and Jarema, 2004 ). Other groups of researchers have applied the analysis of discourse on verbal productions recorded during the classic episodic memory tests as the Wechsler logical memory (Roark et al, 2007 , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that the description of a complex picture is the most widely used task (Goodglass et al, 2000 ; Bschor et al, 2001 ; Cuetos et al, 2009 ; König et al, 2015 ), we observed that the description of a “working day” and “the last dream” seem to be more sensitive tasks, probably because require memory recall and a more structured narration. Some other researchers have investigated different aspects of language as communication abilities (Toledo et al, 2018 ), reading comprehension (Hudon et al, 2006 ; Schmitter-Edgecombe and Creamer, 2010 ), the repetition of complex sentences (König et al, 2015 ; Lust et al, 2015 ) or the ability to recognize the grammatical correctness (Taler and Jarema, 2004 ). Other groups of researchers have applied the analysis of discourse on verbal productions recorded during the classic episodic memory tests as the Wechsler logical memory (Roark et al, 2007 , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Si bien los análisis de discurso son reconocidos como un recurso valioso para el estudio de las dificultades de lenguaje en personas con EA (Lewis, 2016), los antecedentes metodológicos de investigaciones específicas, asociadas con el tema de memoria autobiográfica o preservación de la identidad en la EA, son muy limitados. Análisis del discurso con narrativas de personas con EA a nivel macrolingüístico, destacan el deterioro en la emisión de información relevante en las unidades de contenido, con características como discurso menos informativo, con mayor deterioro en la coherencia global, mayor modalización y estructura narrativa inferior (Toledo, Aluísio, Borges, Dozzi, Sturzeneker, Okada & Lessa, 2017).…”
Section: Marco Metodológicounclassified
“…Las rupturas de turno se deben a la elisión de información que conecta al interlocutor con el tema en cuestión (Ripich & Terell, 1988). Trabajos más recientes han concluido de igual manera que la coherencia global resulta ser una esfera particularmente conflictiva para la población con DTA (Dijkstra, Bourgeois, Allen & Burgio, 2004;Toledo, et. al., 2018).…”
Section: Antecedentesunclassified
“…Es por esto que la variedad de fenómenos en los diferentes niveles de la lengua han motivado nuevos estudios cuyo fin es conformar un catálogo exacto de las características lingüísticas más afectadas o mejor preservadas durante la DTA (Fraser, Meltzer & Rudzicz, 2016;Asgari, Kaye & Dodge, 2017;Hernández-Domínguez, Ratté, Sierra-Martínez & Roche-Bergua, 2018;Toledo, Aluísio, dos Santos, Brucki, Trés, de Oliveira & Mansur, 2018;Toth, Hoffmann, Gosztolya, Vincze, Szatloczki, Banreti & Kálmán, 2018) para dar cuenta del impacto de la demencia en el procesamiento cognitivo de acuerdo a cada etapa (de Lira, Ortiz, Campanha, Bertolucci & Minett, 2011;Ahmed, Haigh, Jager & Garrard, 2013).…”
Section: Introductionunclassified